Study on stress relaxation of simple spiral strand subjected to tensile load based on semi-analytical method. (February 2019) - Zhang, Manman; He, Jing; Meng, Fanming; Gong, Xiansheng
Highlights: The stress relaxation model for the strand is established and solved with the efficient semi-analytical method. The axial force showing the axial load-carrying capacity of the strand decreases gradually with increasing relaxation time. Decreasing the axial tensile strain and helix angle are beneficial to reducing the creep strain of the strand. Increasing the outside wire diameter is beneficial to reducing the creep strain and axial stress of the strand. Abstract: Based on the structural characteristics of the simple spiral strand, the stress relaxation of the strand subjected to tensile load is studied with the semi-analytical method (SAM). In doing so, using the creep and relaxation theories, and elastic theory, the stress relaxation model for the strand is established, into which the Poisson's ratio effect, interwire contact deformation and space spiral contact between wires are incorporated. Meanwhile, the proposed model is validated. Then, the stress relaxation behaviors of the strand are solved with the SAM, in which the conjugate gradient method (CGM) and fast Fourier transform (FFT) are employed for analyzing the contact behavior of the strand. The numerical results show that decreasing the axial tensile strain and the helix angle, and increasing the outside wire diameter are all beneficial to reducing the creep strain and axial stress of the strand. But the latter dealing brings out increments in the contact deformation and contact pressure.